Modifikasi Alat Ripstix Fiberglass untuk Pembelajaran PJOK - Agustina, Rininta; Puspodari; Kholis, Moh. Nur (MAN Insan Cendekia Jambi, 2024)
This research aims to explore the impact of utilizing fiberglass ripstix equipment on students' motivation to learn rhythmic gymnastics. The The Research and Development (R&D) methodology used in this study is based on the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. research participants were fourth-grade students from SDN Betet 3, SDN Ngletih 1, and SDN Banaran 2 in Kediri City. To evaluate the appropriateness of the media., Validation tests were carried out by three specialists: a material expert, a media expert, and a practitioner expert. The study also featured a small-scale trial with 10 students and a large-scale trial involving 40 students. The results of the study are as follows: (1) The material validation received a score of 81.25%, classified as Very Appropriate; the media validation scored 90%, which is also categorized as Very Appropriate; and the practitioner validation reached 95%, indicating it is Very Appropriate. (2) In the trials, the small-scale trial at SDN Betet 3 scored 91.33%, the large-scale trial conducted at SDN Ngletih 1 achieved a score of 91.73%, and the large-scale trial at SDN Banaran 2 scored 89.87%. All these results fall under the Very Feasible category. (3) It was concluded that fiberglass ripstix media is highly suitable for use in PJOK learning without requiring any modifications.